The effects of regions and the wine aging periods on the condensed tannin profiles and the astringency perceptions of Cabernet Sauvignon wines - Qian Tu; Shuzhen Liu; Yuyu Li; Lin Zhang; Zhaoxiang Wang; Chunlong Yuan (Food Chemistry: X, 2022)
This study sought to determine the effects of wine-producing regions and aging periods on the astringency and chemistry of condensed tannins of Cabernet Sauvignon dry red wines. A wine quality study was performed with 5 vintages of 32 Cabernet Sauvignon wines produced in four Chinese wine-producing regions, Hebei (H), Xinjiang (X), Inner Mongolia (NM), and Ningxia (NX). Condensed tannin profiles were assessed by high-performance liquid chromatography coupled with a diode array detector (HPLC-DAD). The (–)-epicatechin as the terminal subunit (tEC) is the major differential component between regions. Correlation analysis revealed that condensed tannin concentration and composition significantly affected the sensory evaluation of astringency. Condensed tannin concentrations were significantly and negatively correlated with wine aging periods. However, no significant correlation was found between aging periods and condensed tannin subunits (as mole%) composition. The current findings enhance the understanding of condensed tannins' chemical and astringency characteristics in Cabernet Sauvignon wines.